1996
DOI: 10.1007/bf00189534
|View full text |Cite
|
Sign up to set email alerts
|

The role of preoperative investigations in predicting difficult laparoscopic cholecystectomies

Abstract: In agreement with data emerging from the literature, the preoperative investigations do not seem to be useful in predicting biliary and vascular complications, whose prevention lies in the adoption of correct surgical technique and a low threshold for conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…This study shows that preoperative ultrasonography can predict the degree of operative difficulty of LC. We found that a thickened GB wall followed by CBD diameter are the most accurate predictors of potential operative difficulty, confirming the experience of European surgeons who reported that a thickened GB wall was associated with a technically difficult operation and prolonged operation time 13,14]. The findings of this study are in accord with those reported by Corr et al, who found a significant association between a thickened GB wall and operative difficulty [1,6,13,14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study shows that preoperative ultrasonography can predict the degree of operative difficulty of LC. We found that a thickened GB wall followed by CBD diameter are the most accurate predictors of potential operative difficulty, confirming the experience of European surgeons who reported that a thickened GB wall was associated with a technically difficult operation and prolonged operation time 13,14]. The findings of this study are in accord with those reported by Corr et al, who found a significant association between a thickened GB wall and operative difficulty [1,6,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…We found that a thickened GB wall followed by CBD diameter are the most accurate predictors of potential operative difficulty, confirming the experience of European surgeons who reported that a thickened GB wall was associated with a technically difficult operation and prolonged operation time 13,14]. The findings of this study are in accord with those reported by Corr et al, who found a significant association between a thickened GB wall and operative difficulty [1,6,13,14]. In a review of a Canadian experience with 2201 LCs there were 95 conversions to open cholecystectomy, giving an overall rate of 4.3% [12].…”
Section: Discussionsupporting
confidence: 87%
“…However, the indications for LC are still limited by technical and anatomical factors, and the importance of preoperative assessment is emphasized to avoid unexpected complications and conversion to an open procedure. 3 Several studies [3][4][5][6][7][8][9][10][11] have predicted the operative conditions and conversion rate of LC from 4 reported that acute cholecystitis, rigidity in the upper abdomen, fever, thickened gallbladder wall on ultrasound, and some laboratory findings were associated with significantly higher conversion rates. In this study, patients in the higher risk groups had a higher conversion rate, but there was no single particular preoperative factor that predicted a high conversion rate.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cholecystitis, male sex, high temperature, high serum lactate dehydrogenase, thickened gallbladder wall on ultrasound, and high white blood cell count could be risk factors for a high conversion rate. [3][4][5][6][7][8][9][10][11] Most factors listed were included in our grading system. Although each factor individually was not sufficient to predict the difficulty of the operation or the risk of conversion, the total number of points accurately represented the actual patient risk for conversion.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients will benefit from the laparoscopic technique as well, but difficult cases have a higher chance of conversion and the consequent complications that could outweigh any benefits of the laparoscopic procedure, rendering it risky, expensive, ineffective, and potentially less effective than open cholecystectomy [7,8]. The preparation and planning of management for patients with symptomatic cholelithiasis would greatly benefit from the availability of reliable predictive factors for difficult procedures, and consequently, conversion of laparoscopic cholecystectomy [9,10]. It is not a complication to convert to an open procedure, and the patient should be informed of this possibility prior to surgery.…”
Section: Introductionmentioning
confidence: 99%

Ultrasound findings in predicting difficult laparoscopic cholecystectomy

Reem Abduljaleel Khaleel Al Thabit,
Mohammed Abd Kadhim Aljuboory,
Sajid Hameed Al-Helfy
2024
GSC Adv. Res. Rev.